Comparison of Executive Functions in Different Phases of Bipolar I Disorder in Patients and General Population - Sabra Mousavizadegan; Mohsen Maroufi (مجله دانشکده پزشکی اصفهان, 2018)
Background: Bipolar I disorder (BID) is a complex and chronic disorder characterized by episodes of mania and depression. Considering the possibility of neuropsychological function deficit in patients with bipolar disorder, the purpose of this study was to determine the mean scores of executive functions (cognitive flexibility and working memory) in mania, euthymia, and depression in bipolar I disorder and compare them with controls.